Pengaruh Digitalisasi terhadap Penjualan Pelaku Usaha Mikro, Kecil, dan Menengah (UMKM) di Kota Makassar - Dedi Harianto; Ahmad Ahmad (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Understanding the impact of digital technology on Micro, Small and Medium Enterprises (UMKM) in Makassar City is the aim of the research. The descriptive qualitative method used in this research is collecting data through observation, interviews and documentation. Research shows that this has a significant positive impact on the profits of UMKM in Makassar City from Digitalization. On the other hand, one of the factors that hinders UMKM actors in terms of the effectiveness of digitalization is the ability to utilize technological media as an indicator of digital economic performance.